Penyuluhan Penegakkan Hukum di Lingkungan Sekolah - Pujilestari, Yulita; Prastini, Endang; Haryanti, Amelia (FKIP Universitas Pamulang, 2019)
Law is the rule of human behavior that is adhered to by society, nowadays violations of the law among the community is often done. In an effort to minimize legal violations in the community, there is a need for counseling on law enforcement in the school environment. Devotion activities aim to assist in cultivating a sense of responsibility in enforcing the law in daily student life. In this devotion, using counseling methods and awareness. The results of community devotion are increased awareness of students to uphold the law both in school and home environment. Advice to the school to involve students directly to enforce the rules of law in schools and communities.